ANALISIS TINGKAT PENGETAHUAN DASAR KOPI TERHADAP POTENSI BISNIS KOPI DI KOTA BANDUNG (PENELITIAN TERHADAP GENERASI MILENIAL) - Dissy Hilmina, - (2020)
Coffee is a drink that has lasted a very long time as a tree drink the world's people demand. In Indonesia itself you can find a coffee culture all over the region. The habits of drinking coffee can be a drink for all circles. In Bandung itself began a lot of coffee shops that were a sign that the coffee industry is now entering the third wave coffee period, where it was marked with rising interest in coffee drinkers on the coffee itself. Either the origin of the seed, the process, or the presentation before the coffee can be drunk. This research is trying to test the basic level of knowledge of the millennial generation in the City of Bandung that can be encouraged to dig up business potential. The business can include coffee plantation, post-harvest coffee, or retail as a coffee shop. From the business that is expected to boost society's economy